2020
DOI: 10.1103/physrevc.101.024004
|View full text |Cite
|
Sign up to set email alerts
|

Time-reversal violation in light nuclei

Abstract: Time Reversal Violation (TRV) interactions between quarks which appear in Standard Model(SM) and beyond-SM theories can induce TRV components in the nucleon-nucleon potential. The effects of these components can be studied by measuring the electric dipole moment (EDM) of light nuclei. In this work we present a complete derivation of the TRV nucleon-nucleon and threenucleon potential up to next-to-next-to leading order (N2LO) in a chiral effective field theory (χEFT) framework. The TRV interaction is then used … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 64 publications
1
27
0
Order By: Relevance
“…More precisely, the PVTV potential at NLO was used in combination with the N 2 LO PCTC potentials from Epelbaum et al [74]. Finally, in Gnech and Viviani [75], the EDMs of deuteron and trinucleons were studied using the χEFT PVTV potential up to N 2 LO along with the N 4 LO PCTC potential of Entem et al [18]. In this paper, it was also shown that the N 2 LO contribution to the PVTV 3N force generated by the three-pion interaction vanishes.…”
Section: The Pvtv Interactionmentioning
confidence: 99%
See 2 more Smart Citations
“…More precisely, the PVTV potential at NLO was used in combination with the N 2 LO PCTC potentials from Epelbaum et al [74]. Finally, in Gnech and Viviani [75], the EDMs of deuteron and trinucleons were studied using the χEFT PVTV potential up to N 2 LO along with the N 4 LO PCTC potential of Entem et al [18]. In this paper, it was also shown that the N 2 LO contribution to the PVTV 3N force generated by the three-pion interaction vanishes.…”
Section: The Pvtv Interactionmentioning
confidence: 99%
“…These can however always be absorbed into a shift ofḡ 0 and of the I = 0 NN operators discussed below. The NLO Lagrangian contains several two-pion two-nucleon PVTV interactions [65,68,69,75], but, for all CP-violating sources, they contribute to the two-and three-body PVTV potentials at N 3 LO and N 2 LO, respectively. We therefore ignore these couplings.…”
Section: The Pvtv Lagrangianmentioning
confidence: 99%
See 1 more Smart Citation
“…Further terms of the Lagrangian involving derivatives would give rise to potential terms which can be reabsorbed in those generated by the Lagrangian given in Eq. (2.1) [17]. Moreover, the calculation of the EDM requires the inclusion of the electromagnetic currents,…”
Section: The Nuclear Trv Potentialmentioning
confidence: 99%
“…Note the huge errors reported for the coefficients a ∆ which are due to the fact that the N2LO diagrams give a correction of ∼ 70%, quite far away from what predicted by chiral perturbation theory. This effect is mainly due to the large contribution of the diagrams in which the c 1 , c 2 , and c 3 LECs [17] of the PC potential appear. We found that the TRV 3-body forces enhanches of the order of ∼ 25% the pure two-body contribution at NLO.…”
Section: The Edm Of 3 H and 3 Hementioning
confidence: 99%